Pengembangan Perangkat Lunak untuk Otomatisasi Pengecekan Format Penulisan Dokumen Jurnal Skripsi menggunakan Fitur Tag pada XML (Studi Kasus JPTIIK FILKOM UB) - Adhitya Wira Castrena; Imam Cholissodin; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Manual document checking process could take up a lot of time and may have a high error margin if it was not done thoroughly. One of its solution is by using an automatic document checker. An automatic document checker by its definition can significantly reduce the process time. In other words, more document can be checked in the same amount of time. In this research, we use journal from JPTIIK, an organization under Faculty of Computer Science, University of Brawijaya, as a base for the application research. The methods used in this research are string matching on the XML document. The program collects metadata that contains informations about the document, such as font types, font sizes, text modification such as bold, italic, or underline, margin, and many other data. This group of metadata will be compared to the set of rules set before on the application, which was based from the template provided by JPTIIK. The result shows that the program could detect mistakes on the journal and write it into a summarized PDF document that can be read easily by the user. The user then can uses this result as a guidance to fix their journal.